Docência em movimento, entrecruzamentos de percursos de vida e percursos docentes: o que acontece com as professoras? - Roncarelli, Isadora Alves (My University, 2019)
This Dissertation has as object of study the teaching as a process of movement and transformation, and it was developed from the listening of ten teachers working at public school of the municipality of Caxias do Sul/RS. The main objective of this research consists of analyzing the levels of satisfaction of teachers in the early years of Primary School throughout their careers and life trajectories, in order to understand how much this satisfaction exerts influences on the pedagogical dimension of teaching performance. The theoretical framework was based on Freire's contributions (1980, 1981, 1996, 1998, 2000, 2009, 2015a, 2015b, 2017), Freire and Faundez (1998), and Freire and Shor (2000), as well as Cunha (2001, 2018), Melucci (2004), Pimenta (2002, 2010), Stecanela (2009a, 2009b, 2016, 2018a, 2018b), Rios (2010), and Lemons (2015). Relationships were established between the transformations experienced in teaching based on reflection on practice and the concept of teaching in motion. The research method was anchored, especially on the Ociology of the Cotidian by Parents (1999, 2013, 2015), through the construction of Emic-Rhythmic Maps, which is a graphic instrument where the teachers enrolled and reported their professional and personal trajectories, also culminating in narratives that were analyzed from the perspective of Discursive Textual Analysis, proposed by Moraes and Galiazzi (2011). From the data constructed in the empirical corpus, five categories emerged that elucidate events experienced by teachers in their personal and professional lives, which intertwined their rhythms of life and rhythms of teaching. The results of the research showed a teaching in motion, permeated by transformations. The permanencies and ruptures in the pedagogical dimension of teaching performance are present in the paths lived by the teachers, and they are affected by events of their personal lives. However, dissatisfaction outside the school does not always reflect on the performance of teachers, because there is a constant exercise in trying to separate their different roles. In the family dimension, the profession exerts a lot of influence, causing concerns, overwork and modifying their ways of being mothers, women, wives, daughters and students.
A presente Dissertação tem como objeto de estudo a docência como processo de movimento e transformação, e desenvolveu-se a partir da escuta de dez professoras atuantes na rede pública de ensino do município de Caxias do Sul/RS. O principal objetivo da pesquisa consiste em analisar os níveis de satisfação de docentes dos anos iniciais do Ensino Fundamental ao longo de suas carreiras e trajetórias de vida, de modo a perceber o quanto essa satisfação exerce influências na dimensão pedagógica da atuação docente. O referencial teórico utilizado teve como base as contribuições de Freire (1980, 1981, 1996, 1998, 2000, 2009, 2015a, 2015b, 2017), de Freire e Faundez (1998), de Freire e Shor (2000), além de Cunha (2001, 2018), Melucci (2004), Pimenta (2002, 2010), Stecanela (2009a, 2009b, 2016, 2018a, 2018b), Rios (2010) e Lemons (2015). Foram estabelecidas relações entre as transformações vividas na docência com base na reflexão sobre a prática e o conceito de docência em movimento. O método de pesquisa ancorou-se, especialmente, na Sociologia do Cotidiano tematizada por Pais (1999, 2013, 2015), por meio da construção de Mapas Emic-Rítmicos, instrumento gráfico no qual as professoras inscreveram e relataram suas trajetórias profissionais e pessoais, culminando também em narrativas que foram analisadas sob a perspectiva da Análise Textual Discursiva, proposta por Moraes e Galiazzi (2011). Dos dados construídos no corpus empírico, emergiram cinco categorias que elucidam acontecimentos vivenciados pelas professoras em suas vidas pessoais e profissionais, os quais entrelaçaram seus ritmos de vida e ritmos da docência. Os resultados da pesquisa evidenciaram uma docência em movimento, permeada por transformações. As permanências e rupturas na dimensão pedagógica da atuação docente estão presentes nos percursos vividos pelas professoras e são afetados por acontecimentos de suas vidas pessoais. Entretanto, nem sempre a insatisfação com o que é vivido fora da escola tem reflexo sobre a atuação das professoras, pois há, constantemente, um exercício de tentativa de separação dos papéis por elas exercidos. Já na dimensão familiar, a profissão exerce bastante influência, causando preocupações, excesso de trabalho e modificando suas formas de serem mães, mulheres, esposas, filhas e estudantes
Keywords: Professores; Prática de ensino; Satisfação no trabalho; Representações sociais; Estilo de vida; Teachers; Student teaching; Job satisfaction; Social representations; Lifestyles